1985
DOI: 10.1111/j.1095-8649.1985.tb03195.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of starvation on RNA: DNA ratios and growth of larval striped bass, Morone saxatalis

Abstract: Hatchery reared larval striped bass, Morone saxarilis, 8-days-post-hatching were subjected to various feeding/starvation regimes over a period of 14 days.Batches of larvae from each treatment were sampled over the 14-day period and subdivided for determination of notochord length and RNA:DNA ratio. The best growth was found in fully fed FlOOO larvae (exposed to 1000 Artermia nauplii 1 -'), which reached 8.2 mm after 11 days and 9.6 mm after 14 days. Starved animals after 1 I days had notochord lengths of 4.9 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 9 publications
3
32
0
Order By: Relevance
“…Our findings are similar to those of other investigations measuring concentrations of nucleic acids in early (larval and YOY) stages of marine fish (e.g. Buckley 1984, Write & Martin 1985, Malloy & Targett 1994, Rooker & Holt 1996, Kuropat et al 2002. The response time of R:D to changes in feeding regime (~3 d, Fig.…”
Section: Biochemical-based Indicators Of Growthsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are similar to those of other investigations measuring concentrations of nucleic acids in early (larval and YOY) stages of marine fish (e.g. Buckley 1984, Write & Martin 1985, Malloy & Targett 1994, Rooker & Holt 1996, Kuropat et al 2002. The response time of R:D to changes in feeding regime (~3 d, Fig.…”
Section: Biochemical-based Indicators Of Growthsupporting
confidence: 91%
“…In early life stages of marine fish, biochemicalbased indicators of growth, including measuring the quantities and/or ratios of nucleic acids (RNA and DNA) and protein in the whole body or specific tissues (e.g. Write & Martin 1985, Malloy & Targett 1994, Rooker & Holt 1996, Kuropat et al 2002, have been used to generate field growth estimates. These indicators have been successfully applied to field-caught cod and haddock larvae (Buckley 1984) and have been measured in larger juvenile cod (Foster et al 1993) but have not been calibrated for age-0 juvenile cod or haddock.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that the RNA:DNA ratio in oysters responds more sluggishly to starvation than in vertebrate systems where significant response times may be as low as 12 h in the case of rat livers (Stocco 1976) or 1 d in fish (Bulow 1970, Wright & Martin 1985.…”
Section: Discussionmentioning
confidence: 97%
“…RNA serves as the machinery required for protein synthesis and the amounts of RNA present have been shown to be directly related to the rate of protein synthesis (Munro & Fleck 1966, Kayes 1979. Work on larval fish by Buckley (1979Buckley ( , 1980Buckley ( , 1982Buckley ( , 1984, Buckley et al (1984) and Wright & Martin (1985) have shown the technique to be rapidly responsive to changes in growth rate, and capable of providing immediate data on growth rate. These properties render the technique particularly suitable for assessing stress in field populations although prior laboratory calibrating is necessary.…”
Section: Of the University Of Maryland Center For Environmental And Ementioning
confidence: 99%
“…High protein content in the gut of the shrimps fed on biofilm was recorded by Tidwell et al (2000). It has been reported that RNA : DNA ratios in body tissues can be used to monitor protein synthesis and growth in fish (Bulow, 1970;Wright and Martin, 1985;Khan and Zafri, 1991). In the present study, higher RNA was recorded in prawns harvested from the substrate based treatments indicating higher protein synthesis and also higher growth.…”
Section: Discussionmentioning
confidence: 98%